Felicia rewrote a quadratic function in vertex form.

h(x)= x2−6x+7

Step 1: h(x)= (x2−6x+ 9 )+7

Step 2: h(x)=(x2−6x+ 9 )+7 −9

Step 3: h(x)=(x−3 )2+2
Felicia said that the vertex is (3, 2). Is Cole correct? If not, identify the step in which Felicia made the mistake and correct her work.

1 answer

Felicia's mistake is in Step 2. The correct step should be:

Step 2: h(x)= (x2−6x+ 9 )+7 −9
Step 2: h(x)= (x2−6x+ 9 ) - 2

With the corrected step, the vertex form of the quadratic function h(x) is:
h(x) = (x - 3)2 - 2

Therefore, the correct vertex is (3, -2), not (3, 2).